Role of information professionals in alleviating student plagiarism for academic integrity in Kenyan universities:: a review of literature - Diki, Paul Mutethia; Gibendi, Ruth (African Journal of Science, Technology and Social Sciences, 2022)
Academic integrity is the commitment and demonstration of honest and moral behavior in an academic setting. This is most relevant at the university level as it relates to providing credit to other people when using their ideas. In simplest terms, it requires acknowledging the contribution of other people. Plagiarism is the act of taking someones else’s work and passing them off as your own. Student plagiarism is a known problem facing universities around the world. Plagiarism is perceived to be a growing problem and universities are being required to devote increasing time and resources to combating it. This fraud behaviour of students in universities is great concern today. As result of explosion of plagiarism among university students, many universities in developed countries have been using technologies to combating deceitful plagiarism behaviour of students. As information literacy experts, information professionals are especially suited to take the lead in educating students about plagiarism and promoting academic integrity. University Librarians working in Kenyan universities can develop information literacy programs to address the issue of student plagiarism. Through combining librarians knowledge of research and information literacy with subject heading, and integrating these skills into the curriculum, students will feel more empowered and competent in their academic assignments. This article will review different types of plagiarism practiced by Kenyan university students and how it affects the integrity of their academic work and how this norm can be alleviated. This study aims to conduct a review of literature on the role of information professionals in alleviating plagiarism in universities in Kenya with a view of suggesting possible solutions to the named problem.